Pengaruh Kecerdasam Intelektual Dan Sikap Kerja Terhadap Kineja Karyawan PT. PLN (PERSERO) UP3 Flores Bagian Timur Kabupaten Sikka - Noviliana Wende; Maria Silvana Mariabel Carcia; Magdalena Silawati Samosir (Jurnal CUAN Universitas Nusa Nipa Maumere, 2023)
The background of this research is the achievement of performance that has not reached the specified target. This study aims to: (1) determine the description of employee performance, Intellectual Intelligence and Work Attitudes; (2) analyzing the effect of Intellectual Intelligence and Work Attitude on employee performance either partially or simultaneously. The population in this study were 50 employees of PT PLN (Persero) UP3 Flores, East of Sikka Regency. Because the population is limited, this research was carried out by means of a census or saturated sampling. Data were collected through questionnaires and analyzed using descriptive methods and inferential statistics, namely multiple linear regression. Hypothesis testing is done through the F test and t test. The results of the descriptive analysis show that the performance variables of Intellectual Intelligence and Work Attitudes are categorized as quite good. The results of the t-test statistics show that partially the Intellectual Intelligence and Work Attitude variables have a positive and significant effect on employee performance. The statistical results of the F test show that simultaneously the Intellectual Intelligence and Work Attitude variables have a significant effect on employee performance. The results of the analysis of determination show that the two independent variables in this study are able to explain the variations in the ups and downs of the performance of employees of PT. PLN (Persero) UP3 Flores, eastern part of Sikka Regency by 58.6%